Fellow Dr. Lamine Doumbia and Prof. Dr. Andrea Behrends - Doumbia, Lamine; Behrends, Andrea (Cluster Conversations, 2022)
Fellow Dr. Lamine Doumbia talks with his host Prof. Dr. Andrea Behrends about his research surrounding urban land governance in West Africa (Dakar, Bamako and Ouagadougou) from a socio-anthropological perspective.